EDUCATION ABOUT THE DANGER OF PESTICIDES FOR THE HEALTH OF FARMERS IN EKATIRO DISTRICT OF BULUKUMBA REGENCY - Muawanah, Muawanah; Rasyid, Nur Qadri; Mu'tamirah, Sitti (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2023)
Pesticides can generally be defined as toxic chemicals used to control nuisance organisms that are detrimental to human interests. In the agricultural sector, pesticides have been found to be useful for increasing agricultural production. However, this use leads to increased side effects. The use of high pesticide doses will automatically be absorbed into the human body, especially farmers, so that it can endanger their health. The greater the chance of exposure to pesticides can increase cases of chronic poisoning in farmers. Farmers can be exposed to pesticides through the skin, inhalation and digestion. The problem faced is that farmers still have low knowledge of the dangers of pesticides for health. Therefore, it is important to carry out outreach which aims to provide education about the dangers of pesticides for the health of farmers in Ekatiro Village, Bulukumba Regency through outreach methods. The conclusion of this extension activity shows that education about the dangers of pesticides for farmers’ health has increased with activity evaluation results obtained by 86%.